Pharmaceutical Innovations and Stewardship Programs in Combating Antimicrobial Resistance - Ousu Merddy; Amit Rahul; Sharma Gupta; James Martin; Sarah Taylor; Matthew Wilson (Journal of Advances in Medicine and Pharmaceutical Sciences, 2024)
This study evaluates the effectiveness of the UK’s AMR Strategy 2019-2024 in combating antimicrobial resistance (AMR), focusing on pharmaceutical innovations. By analyzing trends in human and veterinary antibiotic use alongside resistance rates, the research identifies improvements in reducing antibiotic consumption and resistance, with MRSA resistance declining from 10% in 2016 to 6% in 2023. Despite these positive trends, the research highlights ongoing challenges in the development and implementation of new antibiotics and alternative therapies. Semi-structured interviews with stakeholders, including policymakers and pharmaceutical experts, reveal barriers such as regulatory issues, slow innovation, and insufficient funding for new drug development. The study also examines case studies of pharmaceutical innovations, including β-lactamase inhibitors, bacteriophage therapies, and antimicrobial peptides, noting progress in some areas, but significant gaps in others. The research concludes that while the UK’s AMR Strategy has led to some positive outcomes, further efforts are needed to accelerate the development of novel therapies and address structural barriers in the pharmaceutical sector. Future research should focus on enhancing international collaboration, improving regulatory frameworks, and incentivizing innovation to combat AMR more effectively. Comparative analysis with other countries' strategies could also provide valuable insights for improving the UK’s response to the AMR crisis.